Examining the Efficiency of the Islamic Banking Industry: Comparison of the Covid-19 Period and The New Normal Era in Indonesia - M. Ananda Ikhsan; Kahar Muzakkar; Firman Saputra; Solahuddin Al-Ayubi (International Economic and Finance Review, 2023)
This study aims to examine the efficiency of the Islamic banking industry: a comparison of the COVID-19 period and the new normal era in Indonesia. This study uses Data Envelopment Analysis (DEA) applications that use Variable Return to Scale (VRS) to see the ability of banks to manage input and output variables, especially total financing in Islamic banking in Indonesia. The results of this study show that the average efficiency level of Islamic banks in Indonesia fluctuated during the period before COVID-19 until the New Normal Era. Interestingly, this study found that the overall efficiency level of Islamic banking in Indonesia shows an increasing trend in 2022 with an average efficiency value of 0.66. However, from 2019 to 2020 it experienced a very significant decline. Bank Mualamah Syariah is the bank with the highest efficiency value according to DEA, while Bank BRI Syariah and Bank Tabungan Pensiunan Nasional Syariah have the lowest value. Keywords: Efficiency, Islamic Banking, Data Envelopment Analysis (DEA), Covid-19